War of words Britain, France and discourses of empire during the Second World War - Chin, Rachel 1987- (Cambridge University Press, 2022)
"On 22 June 1940 Marshal Philippe Pétain's newly-constituted French government signed an armistice with Hitler's Germany. At the same time, a relatively unknown Brigadier General named Charles André Joseph Marie de Gaulle fled to London. De Gaulle became the leader of the Free French movement, which resolved to continue fighting against the Axis powers in the name of France. It pursued this battle symbolically, and eventually, militarily. Three decades later, British Members of Parliament would historicise this moment, and the man at its centre. British Prime Minister Edward Heath would describe de Gaulle's "unconquerable determination to restore France" as "one of the few sure and certain things" in 1940. Liberal Party Leader Jeremy Thorpe would recount a story in which Britain's wartime Prime Minister Winston Churchill supposedly greeted de Gaulle with the prophetic words, "here comes the Constable of France."1 In these commemorations, de Gaulle was the undisputed guardian of French honour and the personification of the Franco-British alliance. However, in 1940, and throughout the Second World War, neither de Gaulle's position nor the status of the Franco-British relationship was ever this straightforward"--
Includes bibliographical references and index
EST ca. 08/2022
Keywords: Diplomatische Beziehungen; Zweiter Weltkrieg; Auslandsbeziehungen; Großbritannien; Frankreich; World War, 1939-1945 / Great Britain / Diplomatic history; World War, 1939-1945 / France / Diplomatic history; HISTORY / Europe / Great Britain / General; France / Foreign relations / Great Britain; Great Britain / Foreign relations / 1936-1945; France / Foreign relations / 1914-1940; France / History / German occupation, 1940-1945; Great Britain / Foreign relations / France